FINANCIAL ANALYSIS OF 9-METER FIBERGLASS BOAT CONSTRUCTION AT CV. RONI MARINE SHIPYARD - Kinanti Dzakkiyah Az Zahra; Dwi Putra Yuwandana; Wazir Mawardi (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Fiberglass Reinforced Plastics (FRP) boats are an alternative for fishing boats, providing durability, strength, and ease of production. This study aims to explain the production stages, material requirements, costs estimation, and business feasibility of constructing a 9-meter FRP boat at CV. Roni Marine Boatyard. The research was conducted through direct observation of the the boat construction process, interviews with boatyard staff, measurement of boat dimensions, and cost and financial analysis. The results show that production starts with preparation, fiberglass lamination, installation of wooden parts on the sheer, demolding, installation of internal frames and structural reinforcements, and final finishing. The estimated production cost of one boat unit is IDR 14,364,657. Financial analysis indicates an annual profit of IDR 218,120,568, with an R/C ratio of 1.25, B/C ratio of 1.253, IRR of 124%, a payback period of 0.80 years, and a break-even point of 48 units, demonstrating that the business is feasible and profitable. Key words: business feasibility, Cilacap, fiberglass, FRP boatyard, production cost